A Biophysical Framework of Heat Regulation Strategies for the Design of Biomimetic Building Envelopes. (2015) - Badarnah, Lidia
Abstract: Efficient thermoregulation solutions can be extracted from strategies found in nature. Living organisms maintain body temperature in very narrow ranges in order to survive. Organisms have adopted physiological, morphological, and/or behavioral means for thermoregulation. In some organisms, the process is achieved by skin functioning as a thermal filter, whereas in others, it is achieved by their built structures. Building envelopes separate occupied indoor spaces from the exterior environment are often considered as thermal barriers or shields. Conceiving the envelope in this way limits potentially efficient solutions, where the building envelope is considered as a medium rather than a barrier, just as in living organisms. In this context, biomimetics, as a design approach, provides a huge potential for innovative thermal solutions. This work focuses on the initial phase of a biomimetic design process, where a biophysical framework is established to provide an easier access to relevant analogies. It presents a structured framework of heat regulation processes to support the search for, and the selection of, appropriate strategies from the large database of nature.